Pengelolaan Sampah Rumah Tangga (Studi Kasus di Nagari Saok Laweh Kecamatan Kubung) - Johan, Hane; Ilyasmadi, Ilyasmadi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
This study aims to find, understand and explain the problem as a phenomenon that occurs. The phenomenon in this study is the management of household waste in Nagari Saok Laweh, Kubung District. The results showed that 64% of the respondents acknowledged the very important role of local community leaders, while 36% of the community stated that there was no role from the two governments in terms of providing socialization/training on how to manage waste properly. While 58% of respondents stated that the infrastructure for waste management in Nagari Saok Laweh was still lacking, while the remaining 32% benefited that the infrastructure was sufficient because the community in front of the road was in the trash can, 10% of respondents answered. Community participation in direct waste management 54% of respondents do not carry out environmental management activities directly, and 16% less often, and 7% of respondents quite often and 16% often do waste management.